Fluorine-thiol displacement probes for acetaminophen's hepatotoxicity - Benjamin L. Prather; Shuyue Ji; Yue Zhao; Femil Joseph Shajan; Mi Zhao; Zakey Yusuf Buuh; Robert Maloney; Rui Zhang; Carson Cohen; Rongsheng E. Wang (Elsevier, 2023)
Chemicals possessing reactive electrophiles can denature innate proteins leading to undesired toxicity, and the overdose-induced liver injury by drugs containing electrophiles has been one of the major causes of non-approval and withdraw by the US Food and Drug Administration (FDA). Elucidating the associated proteins could guide the future development of therapeutics to circumvent these drugs' toxicities, but was largely limited by the current probing tools due to the steric hindrance of chemical tags including the common "click chemistry" labels. Taking the widely used non-steroidal anti-inflammatory drug acetaminophen (APAP) as an example, we hereby designed and synthesized an APAP analogue using fluorine as a steric-free label. Cell toxicity studies indicated our analogue has similar activity to the parent drug. This analogue was applied to the mouse hepatocellular proteome together with the corresponding desthiobiotin-SH probe for subsequent fluorine-thiol displacement reactions (FTDRs). This set of probes has enabled the labeling and pull-down of hepatocellular target proteins of the APAP metabolite as validated by Western blotting. Our preliminary validation results supported the interaction of APAP with the thioredoxin protein, which is an important redox protein for normal liver function. These results demonstrated that our probes confer minimal steric perturbation and mimic the compounds of interest, allowing for global profiling of interacting proteins. The fluorine-thiol displacement probing system could emerge as a powerful tool to enable the investigation of drug-protein interactions in complex biological environments.